The Creativity Lab: Interdisciplinary Creativity in Higher Education - Griffith, Anna (Journal of Interdisciplinary Studies in Education, 2023)
This qualitative study explores how educators can foster creativity across disciplines through a conceptual framework for creative interdisciplinary collaboration. The article introduces the Creativity Lab process model, which generates collaboratively developed, multifaceted but cohesive project ideas. The author argues that while creativity and collaboration are recognized as important 21st-century skills, opportunities for learning the granular mechanics of creative interdisciplinary collaboration are not yet fully integrated into higher education. The process model addresses this and offers a practical way to foster creative confidence in participants, encourage pluralities and possibilities through gamification, and emphasize integration and cohesion of multiple perspectives in ideas. The article concludes that educational institutions have an opportunity to build the capacity of students and faculty to become skilled at creative collaborations across disciplines, and the Creativity Lab process model offers a specific approach to doing this.